The gender employment gap: The effects of extended maternity leave policy in Viet Nam - Tu Thi Ngoc Le; Ngoc Thi Bich Pham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study seeks to determine the effect on the gender employment gap and women's employment of the extension of maternity leave from four months to six months in Viet Nam's 2012 Labor Code. To identify this effect, labour market outcomes of groups of women and men are compared. We use the national representative Viet Nam Household Living Standards Survey for 2008-16, with the difference-in-differences approach. The objective of this study is to provide evidence of the relationship between extensions of maternity leave and the gender employment gap in Viet Nam. The findings show that, on average, the new law did not exacerbate the gender employment gap, and there was a narrowing of the gap in the formal jobs sector compared to the waged jobs sector for women of childbearing age without infant children; however, this narrowing is very small. Industry-specific findings show a clear heterogeneity of those effects on the gender employment gap; there are more industries with a wider gap than industries with a narrower gap, and there is evidence of a wider gender gap for women with infants, whereas the gap tends to be narrower for women without infants.
Keywords: J16; J21; 330; gender employment gap; women's employment; maternity leave; waged job; formal job